Analysis of Characteristics and Typology of Mapili Watershed West Sulawesi Province - Wahyudi Isnan; Hasnawir Hasnawir (Jurnal Wasian, 2018)
The multisectoral, multidisciplinary, multi-stakeholder and multidimensional watersheds problems are the consequences of multifunctional watersheds.  The complexity of these problems demanding a system and management approach that appropriate with the characteristics and typology of the watershed. This study aims to analyze the characteristics and typology of Mapili watershed West Sulawesi Province. This research was conducted using surveys, primary, and secondary data collection. Application of geographic information system (GIS) with overlay maps and scoring was used. The results showed that Mapili biogeophysical characterization includes meteorology, morphology, morphometry, hydrology, watershed capability and socioeconomic, cultural and institutional characterization will influence the system of Mapili watershed management. Mapili watershed can be classified into two typology watershed, namely: typology II, which has a low total population density (97 people/km2) with high rainfall (>2500 mm/yr); and typology IV, which has a high total population density (377 people/km2) with low rainfall (<1500 mm/yr). Both typologies have different characteristics of watershed problems. Typology II is generally located in the central area and upstream Mapili and Typology IV are located in the downstream areas of Mapili watershed.Keywords: Watershed characteristic, watershed typology, GIS, Mapili watershed